Factors Affecting the Initial Return of Initial Public Offerings - Nimanussornkul, Chaiwat; Nimanussornkul, Kunsuda (Journal of Business, Innovation and Sustainability (JBIS), 2023)
ratio, that affect the first-day initial return of an initial public offering. The minimum Bayes factor, which had never been used in previous studies, was employed to test the hypothesis instead of P-Value. The analysis was based on a sample of IPOs and related data in the period of March 23rd, 2016 to February 11th, 2021. The results show that the initial return value of Initial Public Offerings (IPOs) was between -25 and 200 percent. The positive initial return was traded in the bull market and had a better financial ratio than the negative initial return. As for the factors ranging from the most to the least strength of evidence against the null hypothesis, investors and persons involved in IPOs should focus on the following factors: a 3-month market return, the return of equity, the price to book value per share ratio, the market capitalization, exchange, the debt to equity ratio, a 1-week market return, the price to earnings per share ratio, a greenshoe option, and the market return.